Småskalig biobränsleeldad kraftvärmeproduktion : teknik och investeringsutrymme - Svensson, Ruben (SLU/Dept. of Energy and Technology, 2011)
To achieve the requirements to decrease emissions of greenhouse gases by 20 % by 2020, Sweden needs to increase its use of bioenergy. In doing so it seems natural that those who already have access to large amounts of biofuels in the form of by-products such as straw, wood chips and digestible materials take advantage of these assets locally. By combining production of heat with power production at the farm it may be possible to not only reduce the direct use of fossil fuel for heating but also reduce energy costs.